Vision rehabilitation workforce in Italy: a country-level analysis - Filippo Amore; Valeria Silvestri; Simona Turco; Stefania Fortini; Andrea Giudiceandrea; Filippo Cruciani; Silvio Paolo Mariotti; Debora Antonini; Stanislao Rizzo (BMC Health Services Research, 2024)
Abstract Background Research and monitoring of human resources available for vision rehabilitation services has been a neglected area of work in the past. This study aims to offer an overview of the vision rehabilitation workforce available in Italy, in order to profile the distribution and number of human resources for vision rehabilitation. Methods Data on the available vision rehabilitation professionals were collected from the yearly report on the state of implementation of policies relating to the prevention of blindness, education and vision rehabilitation, according to a law which was passed by the Italian Ministry of Health, Department of Health Prevention. The report presents a review of all professional workers dealing with low vision rehabilitation centers in Italy between January 2005 and December 2019. Data on the distribution and type of services of government-supported low vision centers across the country were also obtained and examined. Results Of the 289 low vision rehabilitation workers in 2019, 28% were ophthalmologists, 31% orthoptists, 19% psychologists, 17% nurses and 5% social workers. The health workforce densities across the Italian regions ranged from 1.62 to 0.12 per 100.000. The density of vision rehabilitation workers showed a no growing trend from 2006 to 2015. During the study period, it was found a weak but statistically significant association of workforce density with the number of government-supported low vision centers across the Italian territory (r2 = 0.3, p < 0.05). The vision rehabilitation workforce was not associated with the number of low vision patients who accessed to a vision rehabilitation center (r2 = 0.05, p < 0.0001). Discussion A critical review has identified the following national situation: need-based shortages of workers in the vision rehabilitation service sector, as well as deficiencies in data sources. Based on our results, we would recommend increasing the development of human resources trained and dedicated to vision rehabilitation and improve data collection and analysis; provide structural enhancements, across all service levels. These considerations may contribute to the enhancement of policy decisions in order to guarantee an adequate vision rehabilitation workforce and meet national rehabilitation needs. Furthermore, this analysis should be used as a lesson learned by other countries, as low-income ones, in order to develop vision rehabilitation services.